2022
DOI: 10.3390/vaccines11010090
|View full text |Cite
|
Sign up to set email alerts
|

Revaccination in Age-Risk Groups with Sputnik V Is Immunologically Effective and Depends on the Initial Neutralizing SARS-CoV-2 IgG Antibodies Level

Abstract: Vaccination against COVID-19 has occurred in Russia for more than two years. According to the Russian official clinical guidelines to maintain tense immunity in the conditions of the ongoing COVID-19 pandemic, it is necessary to use booster immunization six months after primary vaccination or a previous COVID-19 contraction. It is especially important to ensure the maintenance of protective immunity in the elderly, who are at risk of severe courses of COVID-19. Meanwhile, the immunological effectiveness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Correlation of anti-Spike/RBD antibody levels and neutralizing antibody titers was previously reported ( 6 to 12 ). Here, we evaluated correlation in the Non-COVID group by analyzing levels of specific antibodies and neutralizing antibodies against ancestral SARS-CoV-2.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…Correlation of anti-Spike/RBD antibody levels and neutralizing antibody titers was previously reported ( 6 to 12 ). Here, we evaluated correlation in the Non-COVID group by analyzing levels of specific antibodies and neutralizing antibodies against ancestral SARS-CoV-2.…”
Section: Resultssupporting
confidence: 54%
“…The magnitude of the drop is comparable for both adenovirus and mRNA-based vaccines and was is in the range of 2- to 10-fold decrease between peaking of antibody response (2 to 3 weeks after completion of the vaccination schemes) and 6 months ( 24 , 34 , 35 ). In addition, antibody titers are induced to a similar higher extent in individuals that acquired COVID-19 prior to vaccination compared to naive individuals ( 24 , 34 ), and breakthrough infection boosts the antibody response for both platforms ( 12 , 14 , 15 , 36 ). Finally, partial escape to vaccine-induced antibodies of VOCs Gamma and Delta as assessed by the fold reduction in neutralization titers is also a common feature ( 25 ) and suggests that the continued emergence of VOCs impacts the breadth of protection conferred by vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Sputnik V booster did not result in increased antibody levels in a subgroup of individuals who had recovered from COVID-19 1–4 months prior to a booster. Previously, for Sputnik V revaccination, it was shown that the magnitude of a boost-induced increase in the antibody levels depended on the initial level of antibodies at the time of revaccination [ 24 ]. This effect may have been related to the presence of high levels of specific anti-S antibodies and T-cells, which were sufficient to neutralize the antigen induced by the booster.…”
Section: Discussionmentioning
confidence: 99%